Comparative Analysis of Palliative Sedation and Euthanasia - a literature review - Bednarski, Artur; Krużel, Aleksandra; Ziajor, Seweryn; Sajdak, Piotr; Tomasik, Justyna; Dębik, Marika; Stodolak, Marcel; Szydłowski, Łukasz; Żurowska, Klaudia; Turski, Mikołaj; Kłos, Kamil (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Palliative care is designed to ensure proper comfort in living and dying, primarily by alleviating suffering in patients for whom medical interventions have proved ineffective. In situations where suffering is unbearable, palliative care offers "last resort" treatment, namely palliative sedation. This involves the intentional administration of sedative drugs to the patient to reduce the level of consciousness, even inducing sleep, in order to control suffering caused by conditions that are resistant to other treatments. The aim of this article is to present various perspectives on palliative sedation. Description of the state knowledge: Topics discussed include: cessation of hydration and nutrition, loss of patient control over decision-making in treatment progression after the induction of pharmacological coma, the principle of double effect, complications arising from the use of indiscriminate polypharmacy, and views on life shortening through palliative sedation or its comparison to euthanasia. The distinction between palliative sedation and euthanasia is explored, with arguments on both sides contributing to ongoing debates. The paper concludes by advocating for comprehensive guidelines and interdisciplinary assessments to ensure ethical and patient-centered decision-making in the application of palliative sedation in terminally ill patients. Summary: A discussion is necessary on the creation of acceptable and appropriate procedures that would not arouse the controversies currently associated with the use of palliative sedation.